2015
DOI: 10.1152/ajpcell.00006.2015
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-based antioxidants elicit mitochondrial oxidation via respiratory complex III

Abstract: Excessive oxidation is widely accepted as a precursor to deleterious cellular function. On the other hand, an awareness of the role of reductive stress as a similar pathological insult is emerging. Here we report early dynamic changes in compartmentalized glutathione (GSH) redox potentials in living cells in response to exogenously supplied thiol-based antioxidants. Noninvasive monitoring of intracellular thiol-disulfide exchange via a genetically encoded biosensor targeted to cytosol and mitochondria revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…At the level of the population average, we observed that both the cytosol and mitochondrial matrix experienced an initial reduction in redox potential upon addition of NAC; however, a small oxidative rebound was observed in the mitochondria after several minutes, which was absent in the cytosol (Figure 4). Our population measurement is in agreement with the previous population measurements, and the smaller magnitude of the oxidative rebound likely reflects cell-type differences 40,42 . Furthermore, our measurements also reveal a reductant-specific difference in the stress response because, while NAC-induced stress causes an oxidative rebound in mitochondria only, DTT-induced stress causes an oxidative rebound in both the cytosol and the mitochondria.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…At the level of the population average, we observed that both the cytosol and mitochondrial matrix experienced an initial reduction in redox potential upon addition of NAC; however, a small oxidative rebound was observed in the mitochondria after several minutes, which was absent in the cytosol (Figure 4). Our population measurement is in agreement with the previous population measurements, and the smaller magnitude of the oxidative rebound likely reflects cell-type differences 40,42 . Furthermore, our measurements also reveal a reductant-specific difference in the stress response because, while NAC-induced stress causes an oxidative rebound in mitochondria only, DTT-induced stress causes an oxidative rebound in both the cytosol and the mitochondria.…”
Section: Resultssupporting
confidence: 91%
“…In our initial redox studies (Figure 3), we observed that the Neuro2A cells exhibited an oxidative rebound following DTT addition during the final calibration phase, which indicates that Neuro2A cells respond to reductive stress. It has previously been observed that reductive stress causes a paradoxical oxidative response in HEK293, H9c2, and other cell types 4042 . NAC is a cell-permeant reductant that increases the levels of cytosolic reduced glutathione, but NAC is mitochondrial-lyimpermeant 40,42 .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…MitoSOX Red dye was used to analyze the extent of ROS generation by mitochondria via confocal microscopy as described previously [22]. …”
Section: Methodsmentioning
confidence: 99%